Psychomotor Dance Therapy Intervention (DANCIN) for people with dementia in care homes: a multiple-baseline single-case study. (2nd May 2016) - Guzmán, A.; Freeston, M.; Rochester, L.; Hughes, J. C.; James, I. A.
ABSTRACT: Background: A Psychomotor DANCe Therapy INtervention (DANCIN) using Latin Ballroom (Danzón) in care homes has previously been shown to enhance well-being for both residents with dementia and staff. The aim of this study was to understand the effect of this approach on the mood and behavior of individual people living with mild to moderate dementia. Method: A multiple-baseline single-case study across two care homes and one nursing home with 3–6 weeks baseline, 12-weeks DANCIN (30 minutes/twice-weekly sessions), and 12-weeks follow-up was conducted. Seventeen items from the Dementia Mood Assessment Scale (DMAS) outcome measure were adapted with input from senior staff to match participants' behavior and mood symptoms. Daily monitoring diaries were collected from trained staff on reporting individualized items for ten residents. Data were analyzed, using a non-parametric statistical method known as Percentage of All Non-Overlapping Data (PAND) which provides Phi effect size (ES). Medication use, falls, and life events were registered. Results: Seven residents participated throughout DANCIN whilst three became observers owing to health deterioration. One participant showed adverse effects in three DMAS items. Nine participants, dancers and observers, showed a small to medium magnitude of change (PAND) in 21 DMAS items, indicating a decrease in the frequency of behavior and mood indices which were regarded as problematic; eight items showed no change. Conclusion: Despite methodological challenges, the DANCIN model has the potential to facilitate and sustain behavior change and improve mood (e.g. decrease irritability, increase self-esteem) of the residents living with dementia. The study was conducted in two care homes and one nursing home, strengthening the interventions' validity. Findings suggest DANCIN is appropriate for a larger controlled feasibility study.